The enhancement of mature vessel formation and cardiac function in infarcted hearts using dual growth factor delivery with self-assembling peptides - Kim, Ji Hyun; Jung, Youngmee; Kim, Sang-Heon; Sun, Kyung; Choi, Jaesoon; Kim, Hee Chan; Park, Yongdoo; Kim, Soo Hyun (ELSEVIER SCI LTD, 2011)
For successful treatment of myocardial infarction (MI), it is important to prevent cardiac fibrosis and maintain cardiac function by protecting cardiomyocytes and inducing angiogenesis. To establish functional and stable vessels, various growth factors, ones stimulating both endothelial cells (EC) and vascular smooth muscle cells (VSMC), are required. Self-assembling peptides form fibers (<10 nm) and provide 3-dimensional microenvironments that can recruit EC and VSMC to promote vascularization and long-term delivery of growth factors. Here we demonstrate myocardial protection of infarcted heart using dual growth factor delivery with self-assembling peptides. After coronary artery ligation in rats, growth factors (PDGF-BB and FGF-2) with self-assembling peptides were injected. There were 6 rats in each group. Hearts were harvested at 4 and 8 weeks for functional and histological analysis. Infarct size and cardiomyocyte apoptosis in dual growth factors along with self-assembling peptides group were dramatically reduced compared to sham. The capillary and arterial density of this group recovered with angiogenic synergism and cardiac functions had almost recovered. In conclusion, dual growth factors along with self-assembling peptides lead to myocardial protection, stable vessel formation, and improvement in cardiac function. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: PDGF-BB; VENTRICULAR-FUNCTION; MYOCARDIAL-INFARCTION; ANGIOGENIC FACTORS; PROTEIN THERAPY; BIOMATERIALS; SCAFFOLDS; TISSUE; ARTERIOGENESIS; PROLIFERATION